A nonlinear approach for the determinants of exchange rate volatility: Evidence from Turkey - (:unkn) unknown (Peter Lang AG, 2021)
Emerging markets are reflecting highly volatile exchange rates. Turkish economy, apart from being exposed to exchange rate fluctuations, is fragile due to its dependence on imports. The aim of this paper is to analyze the exchange rate fluctuations in Turkish economy under the following steps: (i) to run principal component-guided sparse regression (PC-LASSO) which is a method for large data to shrink predictions toward the most important variable for volatility out of many potential domestic and international macroeconomic indicators, (ii) to estimate a threshold level for the main determinant of the volatility and examine the impact of these macroeconomic indicators using structural threshold regression model. The empirical findings suggest the international reserves of the central bank as the most important variable for volatility and that the threshold regression reflects the nonlinearity of the model. © Peter Lang GmbH Internationaler Verlag der Wissenschaften Berlin 2020. All rights reserved.
Keywords: Exchange rate; Financial markets; International reserves; PC-LASSO; Threshold regression models